Pengaruh Penggunaan Global Positioning System dan Pengalaman Kerja Kurir Terhadap Ketepatan Pengiriman PT. POS Indonesia KC Tangsel - Sabbir Akhtar; Djoko Hananto (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of Global Positioning System (GPS) use and courier work experience on delivery accuracy. In the logistics and delivery industry, timely delivery is a key focus for logistics companies. In this study, the authors explore how Global Positioning System (GPS) use and courier work experience can improve delivery accuracy. This study employed a quantitative method using a questionnaire as the data collection tool. Questionnaire data was obtained from 52 couriers at PT. Pos Indonesia, South Tangerang Branch. The sampling technique used was non-probability sampling with an associative quantitative approach and primary data. Data analysis was performed using SPSS 27. The results of this study indicate that Global Positioning System (GPS) use has a positive and significant effect on delivery accuracy at PT. Pos Indonesia, South Tangerang Branch. This is indicated by the calculated t-value for this variable in the data processing results being greater than the t-table (7.068 > 2.010). The next variable, Courier Work Experience, also has an effect on delivery accuracy at PT. Pos Indonesia KC Tangerang Selatan has a calculated t-value greater than the t-table (4.115 > 2.010). This indicates that the use of the Global Positioning System and courier work experience can help couriers and companies improve their delivery accuracy.